Symbolic threat affects negative self-conscious emotions. (2020) - Chen, Yujie; Li, Longwei; Ybarra, Oscar; Zhao, Yufang
Abstract: Self-conscious emotions are a distinct category of emotional responses that are rooted in social contexts. Previous findings suggest that negative self-conscious emotions might be elicited by a specific social factor, that is, symbolic intergroup threat. The present study tested the hypothesis that this is true, with three experiments conducted in the Chinese-context. In particular, the Mandarin words for shame (羞愧), guilt (内疚) and loss of face (丢脸) were examined. Symbolic threats were manipulated in all three experiments, with participants randomly divided into a symbolic threat condition and a control condition in each experiment. As expected, participants in the symbolic threat condition always reported more negative self-conscious emotions compared to participants in the control condition. These results suggest that symbolic intergroup threat can lead to self-conscious emotions as well as basic emotions, as was demonstrated by previous research.